å°å°¼åŒ—å¹²å·´é²æ…ˆè¡Œå¦æ ¡åˆä¸éƒ¨æ±‰è¯è¯¾ç½‘ç»œæ•™å¦çŽ°çŠ¶è°ƒæŸ¥ç ”ç©¶ (A Study on Current Situation of Pekanbaru Metta Maitreya Junior High School's Online Chinese Class) - Vina Mettashanti Tionanda; Herman Herman (Asosiasi Program Studi Mandarin Indonesia, 2022)
Â Â Â Â æ‘˜è¦ï¼šæ–°å† çŠ¶ç—…æ¯’ç–«æƒ…â€œé€¼â€äº†å°å°¼å¦æ ¡è¿›è¡Œç½‘ç»œè¿œç¨‹æ•™å¦ï¼ŒåŒ—å¹²å·´é²æ…ˆè¡Œå¦æ ¡åˆä¸éƒ¨ä¹Ÿä¸ä¾‹å¤–ã€‚ä¸ºäº†è§£å°å°¼åŒ—å¹²å·´é²æ…ˆè¡Œå¦æ ¡åˆä¸éƒ¨çš„æ±‰è¯è¯¾ç½‘ç»œæ•™å¦ï¼Œæœ¬æ–‡é€šè¿‡æ–‡çŒ®è°ƒæŸ¥ã€å®žåœ°è§‚å¯Ÿæ³•ã€é—®å·è°ƒæŸ¥æ³•å’Œè®¿è°ˆè°ƒæŸ¥æ³•åˆ†æžè¯¥æ ¡æ±‰è¯ç½‘ç»œæ•™å¦ã€‚å°å°¼åŒ—å¹²å·´é²æ…ˆè¡Œå¦æ ¡åˆä¸éƒ¨ä¸»è¦ç”¨ZOOMä¼šè®®å’Œè°·æŒè¯¾å ‚ä¸¤ç§å¹³å°è¿›è¡Œæ•™å¦ã€‚æ±‰è¯æ•™å¸ˆä½¿ç”¨ â€œä¼ é€’â€”â€”æŽ¥å—å¼â€ æ•™å¦æ¨¡å¼è¿›è¡Œç½‘ç»œæ•™å¦ã€‚æ•™å¸ˆä¸€èˆ¬ä½¿ç”¨è®²è§£åŠ é—®ç”æ³•ã€è®²æ•…äº‹æ³•ã€ç¿»è¯‘æ³•ã€å†™ä½œæ³•ã€ç»ƒä¹ æ³•å’Œè¶£å‘³æ•™å¦æ³•è¿›è¡Œæ•™å¦æ´»åŠ¨ã€‚è°ƒæŸ¥ä¸ä¹Ÿå‘çŽ°ï¼Œé€šè¿‡ç½‘ç»œè¿›è¡Œæ•™å¦ä¹Ÿå½±å“å¦ç”Ÿå¦ä¹ çš„æ€åº¦å’Œå¦ä¹ æ•ˆæžœï¼Œæ¯”å¦‚ï¼šå¦ç”Ÿçš„æ³¨æ„åŠ›éš¾ä»¥é›†ä¸ã€å¦ç”Ÿå¾ˆéš¾è·Ÿè€å¸ˆæ²Ÿé€šã€å¦ç”Ÿæ›´æ¶ˆæžç‰ã€‚å› æ¤æœ¬æ–‡æŽ¨èä¸¤ç§æ•™å¦æ¨¡å¼ï¼Œç»¼åˆæ•™å¦æ¨¡å¼å’Œäº¤äº’å¼æ•™å¦æ¨¡å¼ã€‚Â Â Â Â Â Â Â å…³é”®è¯: æ…ˆè¡Œå¦æ ¡ï¼›æ±‰è¯è¯¾ï¼›ç½‘ç»œæ•™å¦Â Â Â Â Â Â Â Abstract: The Covid-19 pandemic has forced schools in Indonesia to engage in online distance education, including Metta Maitreya Junior High School in Pekanbaru. In order to understand the online teaching of Chinese language lesson in Metta Maitreya Junior High School, Pekanbaru, Indonesia, this study analyzed the online teaching of Chinese language lesson through literature research, field investigation, questionnaire survey and interview investigation. Metta Maitreya Junior High School, Pekanbaru, Indonesia, mainly uses two platforms, Zoom Meetings and Google Classroom, for teaching. In the online learning, Chinese teachers use the â€œTake and Giveâ€ teaching model. Teachers generally used lecture plus question-and-answer method, storytelling method, translation method, writing method, practice method and fun teaching method to conduct teaching activities. The study also found that teaching through the Internet also affects studentsâ€™ learning attitudes and learning result, for example: students difficult to concentrate, students difficult to communicate with teachers, students become more passive, etc. Therefore, this study recommends two teaching models, the comprehensive teaching model and the interactive teaching model.Â Â Â Â Â Â Â Â Â Keywords: Metta Maitreya School; Chinese Language Lesson; Online Teaching